The Advancement of Gas‐Generating Nanoplatforms in Biomedical Fields: Current Frontiers and Future Perspectives. Issue 7 (19th May 2022) - Yan, Jiahui; Wang, Yanan; Song, Xinyu; Yan, Xuefeng; Zhao, Yi; Yu, Liangmin; He, Zhiyu
Abstract: Diverse gases (NO, CO, H2 S, H2, etc.) have been widely applied in the medical intervention of various diseases, including cancer, cardiovascular disease, ischemia‐reperfusion injury, bacterial infection, etc., attributing to their inherent biomedical activities. Although many gases have many biomedical activities, their clinical use is still limited due to the rapid and free diffusion behavior of these gases molecules, which may cause potential side effects and/or ineffective treatment. Gas‐generating nanoplatforms (GGNs) are effective strategies to address the aforementioned challenges of gas therapy by preventing gas production or release at nonspecific sites, enhancing GGNs accumulation at targeted sites, and controlling gas release in response to exogenous (UV, NIR, US, etc.) or endogenous (H2 O2, GSH, pH, etc.) stimuli at the lesion site, further maintaining gas concentration within the effective range and achieving the purpose of disease treatment. This review comprehensively summarizes the advancements of "state‐of‐the‐art" GGNs in the recent three years, with emphasis on the composition, structure, preparation process, and gas release mechanism of the nanocarriers. Furthermore, the therapeutic effects and limitations of GGNs in preclinical studies using cell/animal models are discussed. Overall, this review enlightens the further development of this field and promotes the clinical transformation of gas therapy. Abstract : Gas‐generating nanoplatforms (GGNs) can specifically target the lesion site via the function of targeting moieties, and release gases in response to endogenous stimulation or exogenous stimulation. GGNs can play a diagnostic role (CT, MRI, USI, FI, PAI) to guide the treatment of diseases. At present, gas therapy can be used to treat CDV, IRI, stroke, IBD, cancer, fatty liver, bacterial infection, etc.